Artificial intelligence literacy, sustainability of digital learning and practice achievement: A study of vocational college students - Xuefei Lin; Guangyu Xu; Bin Xiong (PLoS ONE, 2025)
The rapid expansion of AI and the massive use of digital learning are creating a huge change in higher education. In contrast to general higher education, which is at the center of change, the changes in vocational higher education do not seem to have received sufficient attention from researchers. Focusing on artificial intelligence literacy and sustainability of digital learning competences, this study examined the operational behaviors of 1004 students in a practical course in a higher education institution in mainland China by using the COM-B theory. The results showed that AI literacy was positively correlated with sustainable digital learning ability, and AI literacy was positively correlated with students’ sustainable digital learning behaviors through sustainability of digital learning competences. However, students in vocational institutions are not able to translate this learning behavior into a path to achieve good performance in practice, and even sustainability of digital learning competences can be slightly counterproductive. There is no excessive effect on the model after controlling for variables such as gender, family resources, and ethnic minorities, which contributes to benefit equally from quality education.